PEMANFAATAN APLIKASI TUMBUH KEMBANG BALITA (TUKETA) UNTUK MENINGKATKAN EFEKTIFITAS PENGOLAHAN DATA TUMBUH KEMBANG BALITA DI POSYANDU DELIMA KELURAHAN CURUG KULON - Liesnaningsih, Liesnaningsih; Nurnaningsih, Desi; Kurniawan, Arif; Kasoni, Dian (Community Services and Social Work Bulletin, 2021)
Community service is an activity of the academic community that utilizes science and technology to advance the welfare of the community and educate the nation's life. In community service activities in the form of using the TUKETA application to increase the effectiveness of recording the growth and development of toddlers at the Delima Posyandu, Curug Kulon Village, it aims to help posyandu cadres in managing the recording of toddler growth and development. The TUKETA application is designed to increase the effectiveness of recording the growth and development of toddlers previously written by cadres on paper. The target audience in this community service activity are the cadres of the Pomegranate Posyandu, Curug Kulon Village, totaling 7 people and 1 village midwife. Community service activities are carried out by providing training to posyandu cadres and village midwives regarding the use of the TUKETA application. The benefits that can be obtained from this community service activity are to provide convenience for posyandu cadres and village midwives in managing data on growth and development of toddlers at the Delima Posyandu, Curug Kulon Village.